2021
DOI: 10.1111/aogs.14067
|View full text |Cite
|
Sign up to set email alerts
|

Placental abruption in immigrant women in Norway: A population‐based study

Abstract: Objective To estimate the incidence of placental abruption in immigrant women compared with non-immigrants by maternal country and region of birth, reason for immigration and length of residence. Design Nationwide population-based study. Setting Data from the Medical Birth Registry of Norway and Statistics Norway (1990-2016). Sample The study sample included 1,558,174 pregnancies, in which immigrant women accounted for 245,887 pregnancies and 1,312,287 pregnancies were to nonimmigrants. Methods Crude and adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…[ 19 ] While the rate of placental abruption was 3.27% in the entire trauma group in our study, this rate was 12.5% in those who gave birth on the same day as the trauma. Considering that placental abruption is seen at a rate of 0.3%–1% in the normal population,[ 20 ] in our clinic its risk increased in patients, who gave birth on the same day, and also weeks after the traumatic incident. In only 1/5 of the cases with placental abruption in our clinic, placental abruption occurred within the first 24 h on the same day as the trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] While the rate of placental abruption was 3.27% in the entire trauma group in our study, this rate was 12.5% in those who gave birth on the same day as the trauma. Considering that placental abruption is seen at a rate of 0.3%–1% in the normal population,[ 20 ] in our clinic its risk increased in patients, who gave birth on the same day, and also weeks after the traumatic incident. In only 1/5 of the cases with placental abruption in our clinic, placental abruption occurred within the first 24 h on the same day as the trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous Norwegian studies have shown that immigrant women, including Somali, have a higher risk of complications in pregnancy and childbirth, as well as poorer perinatal outcomes when compared to non-immigrant women 5,7 . These risks include pre-term birth, placental abruption, emergency cesarean section, stillbirth, and perinatal death [7][8][9][10][11][12] . Furthermore, Norwegian studies show that Somali women receive less epidural analgesia (EDA) during childbirth compared to both ethnic Norwegian and other immigrant women 10,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Its incidence is higher in Canada and the United States and lower in Norway, Spain, Finland, Sweden, the Netherlands, and Denmark 1 . The overall incidence is approximately 3 to 10 per 1000 births 1,2 . Clinical presentation of placental abruption includes painful vaginal bleeding with uterine contraction and hypertonicity and a non-reassuring fetal heart rate pattern 3 .…”
Section: Introductionmentioning
confidence: 99%